Optimalisasi ketuntasan belajar matematika materi volume bangun ruang melalui pemanfaatan media pembelajaran â€œjamur lubangâ€ bagi siswa kelas VI Sekolah Dasar - Sungatmi, Sri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The background of this research is the grade VI students who are passive when learning mathematics. The average value of mathematics lessons obtained by grade VI students in the material calculates the Volume of Space Build which is material before doing this study is low, namely 55 and the percentage of the number of students who reach the mastery learning standard is only 45%. The purpose of this study is to increase the activity and percentage of mathematics learning for Grade VI students of SD Â Negeri 1 Karanganyar. The research method used was Classroom Action Research (CAR) two cycles and each cycle 2 two meetings through the following stages of planning, obervation and reflection actions within a period of 2 months. Data collection techniques were carried out through observation sheets of each meeting by the observer to see data about learning activities, while data on learning outcomes obtained through daily test scores and mathematics learning achievements of students in cycle 1, and in cycle 2. Based on student mathematics learning achievement data obtained an average grade in the first cycle of 60 increased to 80 in the second cycle. The percentage of students who reached the KKM also increased in the first cycle by 60%, increasing to 70% in the second cycle.